ANALISIS KAPASITAS INVERTER TERHADAP PROTOTYPE SISTEM PELEPASAN BEBAN PADA SISTEM PENYIMPANAN ENERGI - Surga Gunawan, Gusti Ngurah Ary; Dyana Arjana, I Gede; Budiastra, I Nyoman (Jurnal SPEKTRUM; Vol 11 No 3 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i03.p9, 2024)
Solar Power Plants and Wind Power Plants that work with an offgrid system will of course utilize batteries to store the energy that has been produced. The aim of this research This project seeks to create a prototype that applies a load shedding system for energy storage, utilizing the ATmega 328, ESP32 microcontroller with inverter selection to see its effectiveness from the time data obtained and to find out the performance results of the load shedding design for energy storage in terms of its effectiveness. The design of a prototype load shedding system for ATmega 328 microcontroller-based energy storage and an ESP32-based early warning system applies 4 load classifications, namely prioritas load, class 1 load, class 2 load, and class 3 load. This research found that the results of using a load shedding system The ATmega 328 microcontroller-based energy storage can extend the life time of prioritas load lamps compared to other load classes. A comparison of an inverter with a power of 1000 Watts and an inverter with a power of 1500 Watts produces different results, there is a time difference of 34 minutes. An inverter with 1500 Watt power goes out more quickly for prioritas loads so that when operating this inverter, precise calculations are needed to avoid large power losses. The choice of 1000 watt and 1500 watt inverters was chosen based on the load used in the designed prototype, namely 4 100 watt incandescent lamps with a total of 400 watts, taking into account the efficiency of the inverter device which is in the range of 80%.